Endonasal endoscopic resection of intranasal haemangioma - Raja Lope Ahmad, Raja Ahmad Al'konee; Kamarudin, Norie Azilah (Malaysian Medical Associations, 2006)
Intranasal haemangioma is quite rare. This tumor may be confused with other intranasal vascular tumor such as juvenile nasopharyngeal angiofibroma (JNA), glomus tumor as well as other tumor such as angiosarcoma and leiomyoma. Juvenile nasopharyngeal angiofibroma is the most common vascular tumor encountered in nasal cavity. A definitive histology diagnosis pre-operatively is difficult to be obtained as the biopsy may lead into severe uncontrolled bleeding. The final diagnosis very much depends on histology after the tumor excision. Complete surgical resection of the tumor is the standard approach. In this report we describe our surgical management in approaching intranasal haemangioma endoscopically and this pathology can be considered as one of differential diagnosis for unilateral nasal mass.